The zoonotic protozoan of sheep carcasses in the north of Algeria: A case of ovine toxoplasmosis - DAHMANI, A.; HARHOURA, K.; AISSI, M.; ZENIA, S.; HAMRIOURI, B.; GUECHI, N.; AIT ATHMANE, M.; KADOUR, R. (Journal of the Hellenic Veterinary Medical Society, 2018)
Toxoplasma gondii is a zoonotic protozoan parasite of great importance in veterinary and public health. The aim of the present study was to determine the seroprevalence for T. gondii in 580 sheep sera slaughtered for human consumption in the slaughterhouses of El Harrach by a commercial kit ELISA (enzyme-linked immunosorbent assay), and to evaluate the presence of T.gondii in 335 sheep from 580 (335 oesophagi and 335 diaphragms) by.the histopathological analysis. Antibodies to T. gondii were found in 8.28% (48 /580) of sheep. All positive sheep were male. Seropositivity for T. gondii increased with age, but the difference was not statistically significant.. While the seroprevalence was significantly higher in summer and in the North /Center of Algeria. Thus, season and origine of animals were considered as risk factors associated with T. gondii infection. Histopathological analysis showed that only 2 sheep presented dubious cysts of T. gondii. However, tissues cysts compatible with Sarcocystis spp. were visible in the histological sections of 94.03% (315/335) of sheep. These results suggest that infection with T. gondii in sheep is present in the north of Algeria and as sheep with antibodies usually carry tissue cysts, this indicates that undercooked lamb and mutton may indeed be a sources of human toxoplasmosis.